Taking up the climate change challenge: A new perspective on central banking - Paola D'Orazio; Lilit Popoyan (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
The awareness about climate-related financial risks is gaining momentum both in the policy and academic debates. The role of countries' institutional dimension and central bank governance structures in the adoption of green prudential regulation is, however, overlooked in the current discussion. The paper fills this gap by proposing an analysis of the state-of-the-art, challenges and perspectives, of ''green'' central banking. The study complements existing research that usually points to an ''extended'' monetary policy mandate, including, for example, sustainability objectives or green growth, as the primary motivation for a central bank to engage in ''green'' financial policymaking. According to our research, the decision to implement green regulations is not exclusively related to the mandate per se, but on the central bank's independence and on how the interaction between the monetary and prudential policy is structured. Moreover, the higher exposure to climate-related adverse events also plays a crucial role in the adoption of green prudential regulations. To avoid potential conflicts between monetary policy and green prudential regulation caused by existing intertwined transmission mechanisms, on the one hand, our analysis emphasizes the importance of having a central bank that hosts the green prudential regulation under its governance roof. On the other hand, when the ''green'' governance models studied in the paper are in place, the Tinbergen principle is safeguarded.
Keywords: G28; E58; Q54; Q56; Q58; 330; Central banking; Policy mandate; Macroprudential policy; Central bank governance; Climate change